Traumatic Transection of the Pancreas. A Case of Delayed Presentation - Levine, Rebecca A; Bank, Matthew A (JOP. Journal of the Pancreas, 2011)
Context Isolated traumatic injuries to the pancreas are extremely unusual and diagnosis may be difficult due to delay in presentation and subtlety of symptoms. Case report We describe a patient who presented 24 hours after sustaining blunt abdominal trauma and was found to have a complete pancreatic neck transection on computed tomography with no other injuries. The patient underwent a distal pancreatectomy and splenectomy which was complicated by a postoperative abscess on day 15. This was treated with percutaneous drainage and he has recovered well. Conclusion Pancreatic transection in the absence of associated injuries is rarely seen after blunt trauma but can result in devastating outcomes if left unrecognized. A high index of suspicion and early intervention are critical. Image: Transection at the junction of the pancreatic neck and body.